Rotunda na Kopcu Krakusa? - Słupecki, Leszek P. (Folia Praehistorica Posnaniensia, 2020)
The paper focuses on the question of a mysterious building on the top of Krakus burial mound (Cracow, Poland) which was documented on some engravings from the late 16th and 17th century presenting panoramas of the city of Cracow (Matthäus Merian, 1617; and Eric Dahlberg, 1655). On the Swedish map from 1702 the top of the mound is already empty. The hypothesis is that probably a small Romanesque rotunda stood there. The facility established over a big burial mound resembles the case of St. Nicholas (Sv. Nikola) church in Nin (Croatia) which is an early Romanesque rotunda (triconchos) rom ca. 1100 AD which stands till today on the top of a prehistoric mound. In Cracow excavation done on Krakus mound in 30ties eventually revealed a negative of destroyed foundations od the rotunda, which remained uninterpreted.